Two-phase system for the clean and high yield synthesis of furylmethane derivatives over- SO3H functionalized ionic liquids - Shinde, S. H.; Rode, C. V. (Green Chemistry, 2017)
A new and effective unique two-phase reaction system is investigated for the high yield production of tri(furyl) methane from furfural and furan. This strategy includes the use of an acidic aqueous phase (water + -SO3H functionalized IL) and furan phase, which significantly suppresses polymer formation, thereby increasing the yield of tri(furyl) methane. Furan serves as a reactant as well as an extraction solvent for the recovery of the condensation products. For comparison, different -SO3H functionalized ionic liquids are prepared and their performances evaluated for the condensation of furan and furfural. The ionic liquids with alkyl chain linkers are found to be more effective and acidic than those with imidazolium linked N-sulfonic acids. In addition, an increase in carbon chain length between imidazole/tri-ethylamine/pyridine and -SO3H, increases the catalytic activity of the respective ionic liquids. Among the several prepared ionic liquids, the strongly acidic imidazolium based butylsulfonic acid 6 shows the best activity with a maximum condensation product yield of 84%. This strategy offers a significantly high yield of the condensation products of furan and furfural compared to the traditional mineral acid route. The activity and stability of the -SO3H functionalized 6 is confirmed from seven successful recycles, in which there is no reduction in its activity. Finally, this new strategy is successfully extended for the condensation of furan derivatives (e. g. furan and 2-methylfuran) with several different aldehydes, ketones and alcohols.